Nucleation and growth of hierarchical martensite in epitaxial shape memory films. (15th June 2017) - Niemann, R.; Backen, A.; Kauffmann-Weiss, S.; Behler, C.; Rößler, U.K.; Seiner, H.; Heczko, O.; Nielsch, K.; Schultz, L.; Fähler, S.
Abstract: Shape memory alloys often show a complex hierarchical morphology in the martensitic state. To understand the formation of this twin-within-twins microstructure, we examine epitaxial Ni-Mn-Ga films as a model system. In-situ scanning electron microscopy experiments show beautiful complex twinning patterns with a number of different mesoscopic and macroscopic twin boundaries between already twinned regions. We explain the appearance and geometry of these patterns by constructing an internally twinned martensitic nucleus, which can take the shape of a diamond or a parallelogram, within the basic phenomenological theory of martensite. These nucleus contains already the seeds of different possible mesoscopic twin boundaries. Nucleation and growth of these nuclei determines the creation of the hierarchical space-filling martensitic microstructure. This is in contrast to previous approaches to explain a hierarchical martensitic microstructure. This new picture of creation and anisotropic, well-oriented growth of twinned martensitic nuclei explains the morphology and exact geometrical features of our experimentally observed twins-within-twins microstructure on the meso- and macroscopic scale. Graphical abstract: Image 1